Analisis Modul Ajar Fisika berbasis Kearifan Lokal pada Platform Merdeka Mengajar - Resti Warliani; Asep Irvan Irvani; Asep Khoiril (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
The learning process in the Kurikulum Merdeka ensures that the learning practices are student-centered. The focus of this curriculum is the revival of learning. One important point in this new curriculum is Modul Ajar. Modul Ajar has significant role in the success of learning process, especially in the subject of Physics. The government provides guidelines for the development, along with several samples, because in this curriculum, teachers are given the authority to develop the Modul Ajar based on characters and needs of the students. This matter creates new problem which is the teacher difficulty on developing Modul Ajar in accordance to government guidelines, student characters, and also different school environtments. Modul ajar in Merdeka Mengajar platform are still limited. Therefore, the researcher proposes to analyze the Physics Modul Ajar in Merdeka Platform in the context of Local Wisdom as a Needs Analysis for the development of future Modul Ajar. This local wisdom aligns with Profil Pelajar Pancasila, which is one of the key components of Kurikulum Merdeka. The method used in this research is Document Analysis method and surveys. Document Analysis includes the analysis of the availability of Modul Ajar in Merdeka Mengajar Platform, which contains General Information, Core Component, and Attachments. A survey was conducted among 57 Physics teachers. The survey point out that 82,5% of the respondents consider the Merdeka Mengajar Platform as a reference for developing of Modul Ajar.